Do state characteristics matter? State level factors related to tobacco cessation quitlines. (29th November 2007) - Keller, Paula A; Koss, Kalsea J; Baker, Timothy B; Bailey, Linda A; Fiore, Michael C
Abstract : Background: Quitline services are an effective population-wide tobacco cessation strategy adopted widely in the United States as part of state comprehensive tobacco control efforts. Despite widespread evidence supporting quitlines' effectiveness, many states lack sufficient financial resources to adequately fund and promote this service. Efforts to augment state tobacco control efforts might be fostered by greater knowledge of state level factors associated with the funding and implementation of those efforts. Methods: We analysed data from the 2004 North American Quitline Consortium survey and from publicly available sources to identify state level factors related to quitline implementation and funding. Factors included in the analyses were state demographic characteristics, tobacco use variables, state tobacco control spending, and economic and political climate variables. Univariate and multivariate regression analyses were conducted. Results: The best fitting multivariate model that significantly predicted the presence or absence of a state quitline included only cigarette excise tax rate (p = 0.020). In terms of funding levels, states with high rates of cigarette consumption (p = 0.047) and with higher per capita expenditures for tobacco control programmes (p = 0 .0.004) were most likely to spend more on per capita operations budget for quitlines. Conclusion: State level factors appear to play a part in whether states had established quitlines by mid-2004 and the amount of per capita quitline funding.